Pengaruh Penambahan Rempah Jintan Putih (Cuminum cyminum L.) Terhadap Cita Rasa Pada Rendang Daging Sapi Dengan Uji Hedonik - Rinata, Taufik Maulana; Iswendi, Iswendi; Iryani, Iryani; Amelia, Fitri (Departemen Kimia FMIPA UNP, 2023)
Beef rendang is one of traditional foods from Minangkabau, West Sumatra. Rendang cooked with basic ingredient from beef, coconut milk and special spices. The addition of cumin (Cuminum cyminum L.) spice in cooking can improve the taste, other than that, cumin is additionally valuable as an antioxidant, antidiabetic, and lowering cholesterol. Nevertheless, there is no organoleptic report stating that cumin spice can improve the taste of rendang. The aim of the study was to see the level of preference for rendang which was added weight variations of cumin based on sensory parameters (color, meat texture, surface of spices, aroma, flavor). The test method determined organoleptically by the hedonic test method on 48 panelists from chemistry 3rd year understudies of University of Negeri Padang were given rendang with variations in addition of cumin at 0, 0.5, 1, 1.5, 2, 2.5 grams/500 grams of beef. The test results appeared a significant decrease in the level of inclination for rendang in parameters of color, surface of spices, and flavor of rendang with the addition of 2.5 grams of cumin when compared to the original rendang and and in common there was no significant alter. In conclusion, the expansion of cumin flavor influences the taste of beef rendang.